Insula-Retrosplenial Cortex Overconnectivity Increases Internalizing Via Reduced Insight in Autism - Hogeveen, Jeremy (Biol Psychiatry, 2018)
BACKGROUND: Internalizing symptoms like anxiety and depression are common and impairing in autism spectrum disorder (ASD). Here, we test the hypothesis that aberrant functional connectivity between three brain networks [salience network (SN), default-mode network (DMN), and frontoparietal network (FPN)] plays a role in the pathophysiology of internalizing in ASD. METHODS: We examined the association between resting-state functional connectivity and internalizing in 102 adolescents and young adults with ASD (N=49) or typical development (TYP; N=53). Seed-to-target functional connectivity was contrasted between ASD and TYP using a recent parcellation of the human cerebral cortex, and connections that were aberrant in ASD were analyzed dimensionally as a function of parent-reported internalizing symptoms. RESULTS: Three connections demonstrated robust overconnectivity in ASD: i) anterior insula to retrosplenial cortex (i.e. SN-DMN), ii) anterior insula to frontal pole (i.e. SN-FPN), and iii) dorsolateral prefrontal cortex to retrosplenial cortex (i.e. FPN-DMN). These differences remained significant after controlling for age, and no age-related effects survived correction. The SN-DMN connection was associated with greater internalizing in ASD, mediated by a bigger difference between self- and parent-reported internalizing. Control analyses found that the other two connections were not associated with internalizing, and SN-DMN connectivity was not associated with a well-matched control measure (externalizing symptoms). CONCLUSIONS: The present findings provide novel evidence for a specific link between SN-DMN overconnectivity and internalizing in ASD. Further, the mediation results suggest that intact anterior insula-retrosplenial connectivity may play a role in generating insight into ones’ own psychopathology.